Familial Temperature-Sensitive Auditory Neuropathy: Distinctive Clinical Courses Caused by Variants of the OTOF Gene - Zhu, Yi-Ming; Li, Qi; Gao, Xue; Li, Yan-Fei; Liu, You-Li; Dai, Pu; Li, Xiang-Ping (Frontiers in Cell and Developmental Biology, 2021)
Objective: To investigate the clinical course and genetic etiology of familial temperature-sensitive auditory neuropathy (TSAN), which is a very rare subtype of auditory neuropathy (AN) that involves an elevation of hearing thresholds due to an increase in the core body temperature, and to evaluate the genotype–phenotype correlations in a family with TSAN. Methods: Six members of a nonconsanguineous Chinese family, including four siblings complaining of communication difficulties when febrile, were enrolled in this study. The clinical and audiological profiles of the four siblings were fully evaluated during both febrile and afebrile episodes, and the genetic etiology of hearing loss (HL) was explored using next-generation sequencing (NGS) technology. Their parents, who had no complaints of fluctuating HL due to body temperature variation, were enrolled for the genetics portion only. Results: Audiological tests during the patients' febrile episodes met the classical diagnostic criteria for AN, including mild HL, poor speech discrimination, preserved cochlear microphonics (CMs), and absent auditory brainstem responses (ABRs). Importantly, unlike the pattern observed in previously reported cases of TSAN, the ABRs and electrocochleography (ECochG) signals of our patients improved to normal during afebrile periods. Genetic analysis identified a compound heterozygous variant of the OTOF gene (which encodes the otoferlin protein), including one previously reported pathogenic variant, c.5098G>C (p.Glu1700Gln), and one novel variant, c.4882C>A (p.Pro1628Thr). Neither of the identified variants affected the C2 domains related to the main function of otoferlin. Both variants faithfully cosegregated with TSAN within the pedigree, suggesting that OTOF is the causative gene of the autosomal recessive trait segregation in this family. Conclusion: The presence of CMs with absent (or markedly abnormal) ABRs is a reliable criterion for diagnosing AN. The severity of the phenotype caused by dysfunctional neurotransmitter release in TSAN may reflect variants that alter the C2 domains of otoferlin. The observations from this study enrich the current understanding of the phenotype and genotype of TSAN and may lay a foundation for further research on its pathogenesis.